Patient and Caregiver Perceptions of Caregiving Contributions During Cancer Clinical Trials: A Mixed‐Methods Study - Janine Cerutti; Maria C. Lent; Randall F. Holcombe; Maija Reblin (Cancer Medicine)
ABSTRACT Objective Caregivers play crucial roles in cancer treatment and outcomes. However, little is known regarding how caregivers support patients during cancer clinical trials. The aim of this study was to gain insight into the caregiver experience of rural and urban patients enrolled in cancer clinical trials. Methods As part of a quality improvement study, 21 patient–caregiver dyads were interviewed using closed and open‐ended interview questions. We analyzed quantitative and qualitative data on patient and caregiver perceptions of caregiver contributions and explored differences in the reported caregiving experience between rural and urban participants. Results While patient–caregiver dyads showed significant disagreement in the symptoms/medication management domain, with caregivers tending to acknowledge the contribution while patients did not (χ2 (1, 21) = 5.82, p = 0.016), both groups generally showed agreement in their perceptions of caregiver involvement and reported similar levels of involvement across the other six assessed domains. Qualitative analysis revealed three themes: patient independence, invisible support, and accepted forms of support. Despite patients valuing independence, patients benefited from caregivers' unseen support, and providing emotional support and attending appointments were widely accepted forms of support among patients. No meaningful differences in caregiver contributions were found between rural and urban patient–caregiver dyads. Conclusion Our study revealed that caregivers are assisting patients in often unseen and underestimated ways during cancer clinical trials, highlighting their multifaceted role. Cancer clinical trials should implement a family‐centered approach, especially for rural caregivers, to enhance patient retention and outcomes.